Effects of parental migration on the education of left-behind children - Jabbar, Jeenat Binta (Technium Social Sciences Journal, 2022)
This study investigates the effects of remittances and migration on the school dropout rate of left-behind children in rural Bangladesh. Using household survey data from a two-wave panel, conducted by Bangladesh Integrated Household Survey (BIHS) in 2011 and 2015, this study combines the fixed-effects approach with a linear probability model and instrumental variable (IV) strategy to control for the possible endogeneity of migration and remittances. The estimated results show that children from remittance-receiving households are less likely to drop out of school, while parental migration has substantial disruptive effects. Heterogenous analysis indicates that boys seem to benefit from remittances in both primary and secondary school. However, girls do not move beyond primary education even when the household receives additional funds from remittances. The findings also suggest that remittances relax the poor households' budget constraints, making it easier for them to invest in their children. In contrast, the effect of remittances is insignificant for children in wealthier households. Therefore, the results may provide some guidance for policymakers in their efforts to increase the school attainment of children, especially for those who live in migrant households.